Interoception and Obsessive-Compulsive Disorder: A Review of Current Evidence and Future Directions - Bragdon, Laura B.; Eng, Goi Khia; Belanger, Amanda; Collins, Katherine A.; Stern, Emily R. (Frontiers in Psychiatry, 2021)
Disrupted interoceptive processes are present in a range of psychiatric conditions, and there is a small but growing body of research on the role of interoception in obsessive-compulsive disorder (OCD). In this review, we outline dimensions of interoception and review current literature on the processing of internal bodily sensations within OCD. Investigations in OCD utilizing objective measures of interoception are limited and results mixed, however, the subjective experience of internal bodily sensations appears to be atypical and relate to specific patterns of symptom dimensions. Further, neuroimaging investigations suggest that interoception is related to core features of OCD, particularly sensory phenomena and disgust. Interoception is discussed in the context of treatment by presenting an overview of existing interventions and suggesting how modifications aimed at better targeting interoceptive processes could serve to optimize outcomes. Interoception represents a promising direction for multimethod research in OCD which we expect will prove useful for improving current interventions and identifying new treatment targets.